Developing COUNTER standards to measure the use of Open Access resources - Greene, Joseph W. (Qualitative and Quantitative Methods in Libraries, 2019)
There are currently no standards for measuring the use of open digital content, including cultural heritage materials, research data, institutional repositories and open access journals. Such standards would enable libraries and publishers that invest in open digital infrastructure to make evidence-based decisions and demonstrate the return on this investment. The most closely related standard, the COUNTER Code of Practice (CoP), was designed for subscription access e-resources and ensures that publishers provide consistent, credible and comparable usage data. In the open environment, computer programs known as web robots constantly download open content and must be filtered out of usage statistics. The COUNTER Robots Working Group has recently been formed to address this problem and to recommend robot detection techniques that are accurate, applicable and feasible for any provider of open content. Once accepted, they will be incorporated into the COUNTER CoP 5. In this paper we describe the overall goals of the analysis, the scope and techniques for building the dataset and the robot detection techniques under investigation.